The Impact of Economic Security on Sustainable Entrepreneurship in Central and Eastern Europe – from the Financial Crisis to the COVID–19 Pandemic - Kowalska, Magdalena; Misztal, Anna; Matera, Rafał (Comparative Economic Research. Central and Eastern Europe, 2024)
The article’s main aim is to assess the impact of economic security on sustainable entrepreneurship in Central and Eastern European Countries (CEECs), including Bulgaria, Croatia, Czechia, Estonia, Hungary, Lithuania, Latvia, Poland, Romania, Slovakia and Slovenia from 2008 to 2020. The paper’s novelty is the development of indicators of sustainable entrepreneurship and its three pillars: economic, social and environmental. Moreover, we assessed the impact of economic security on sustainable entrepreneurship and conducted a comparative analysis of its consequences on the economic, social and environmental components of entrepreneurship. We use the Pearson correlation coefficient, the Ordinary Least Square Method, and the SUR estimations for structural equations. The results of the analysis indicate that sustainable entrepreneurship and economic security in the analysed countries are growing. However, their dynamics are varied, and what is more, economic security has a statistically significant impact on sustainable entrepreneurship. The impact of economic security on sustainable entrepreneurship from 2008 to 2020 is highest in Slovakia, Bulgaria and Poland. The lowest is in Latvia, Romania and Czechia. We notice that pursuing a stable and responsible macroeconomic policy affects the implementation of sustainable development goals. It is important to create the best conditions for growth in the long term, which is a challenge because of the problem of finding optimal relationships between factors that determine economic security.